2019
DOI: 10.1055/s-0039-1683853
|View full text |Cite
|
Sign up to set email alerts
|

Tailored Medical Management of the Complex Postoperative Crohn's Disease Patient

Abstract: Despite advancements in medical therapy, many patients with Crohn's disease continue to require surgery for intestinal resection and/or management of perianal disease at some point in their disease course. Unfortunately, in this complex group of patients, postoperative disease recurrence rates are high. Medical prophylaxis can be used to prevent Crohn's disease recurrence or manage residual disease after surgery, but the ideal timing to start medications after surgery varies based on patient risk factors and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
(49 reference statements)
0
1
2
Order By: Relevance
“…Furthermore, smoking was associated with endoscopic, clinical, and surgical recurrence. Achkar et al reported that perianal lesions, smoking, internal fistula, perforation, and abdominal abscess were all independent risk factors 33. However, the present study did not indicate that smoking and perianal lesions are independent risk factors; that may be because patients in this study were generally young, highly educated, and less likely to smoke than in other countries.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, smoking was associated with endoscopic, clinical, and surgical recurrence. Achkar et al reported that perianal lesions, smoking, internal fistula, perforation, and abdominal abscess were all independent risk factors 33. However, the present study did not indicate that smoking and perianal lesions are independent risk factors; that may be because patients in this study were generally young, highly educated, and less likely to smoke than in other countries.…”
Section: Discussioncontrasting
confidence: 88%
“…Achkar et al reported that perianal lesions, smoking, internal fistula, perforation, and abdominal abscess were all independent risk factors. 33 However, the present study did not indicate that smoking and perianal lesions are independent risk factors; that may be because patients in this study were generally young, highly educated, and less likely to smoke than in other countries. In addition, some patients do not pay attention to perianal diseases and treat them as ordinary hemorrhoids, and so this factor remains to be elucidated in future research.…”
Section: Discussioncontrasting
confidence: 83%
“…Such tools include smoking status, disease phenotype, and surgical history. 2,6 Factors such as surgical anastomosis type and length of bowel resected are less well-replicated, often limited by heterogeneity between cohorts or small sample sizes. In this issue of the Journal, Tandon et al 7 present a rigorous metaanalysis examining the role of histologic features in predicting postoperative recurrence in CD.…”
mentioning
confidence: 99%